An Improved LC-MS/MS Method for Simultaneous Determination of the Eleven Bioactive Constituents for Quality Control of Radix Angelicae Pubescentis and Its Related Preparations - Jin Li; Qiu-Hong Zhang; Jun He; Er-wei Liu; Xiu-mei Gao; Yan-xu Chang (The Scientific World Journal)
An improved LC-MS/MS method was developed for simultaneous determination of eleven bioactive constituents of Radix Angelicae Pubescentis and its related preparations. It was the first report on the quantification of bioactive constituents in different preparations of Radix Angelicae Pubescentis by LC-MS/MS analytical method. These samples were separated with an Agilent Zorbax Extend reversed-phase C18 column (1.8 μm, 4.6 × 100 mm) by linear gradient elution using aqueous ammonium acetate and acetonitrile as mobile phase. The flow rate was 0.3 mL min−1. The eleven bioactive constituents showed good regression (R>0.990) within test ranges and the recoveries were in the range of 87.1–110%. The limit of detections and quantifications for most of the major constituents were less than 0.5 and 1.0 ng mL−1, respectively. All results indicated that the developed method could be readily utilized as a suitable quality control method for Radix Angelicae Pubescentis and related preparations.